Efektivitas Konseling Kelompok dengan Teknik Restrukturisasi Kognitif dalam Mengurangi Isolasi Sosial pada Siswa Korban Bullying di SMA Tunas Kelapa Samarinda - Apriana Hasriana Putri (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
This study aims to determine the effectiveness of Cognitive Behavioral Therapy (CBT)-based group counseling services with cognitive restructuring techniques in reducing the level of social isolation in students who are victims of bullying. This study uses a quantitative approach with a pre-experimental design in the form of a one-group pretest-posttest design. The research subjects were 3 students selected using a purposive sampling technique with the criteria of students being victims of bullying, having a high level of social isolation based on the pretest results, and being willing to participate in the entire series of interventions. The research instrument used a social isolation scale questionnaire in the form of a Likert scale that had been tested for content validity through expert judgment and its reliability using the Cronbach's Alpha coefficient. Measurements were taken before (pretest) and after (posttest) the treatment was given. The intervention was given in the form of CBT-based group counseling with cognitive restructuring techniques implemented in several sessions, including identifying negative thoughts due to bullying, cognitive restructuring to replace irrational thoughts with more adaptive ones, and social skills training to improve student interaction. Data were analyzed using a paired sample t-test with a significance level of 0.05. The results showed a difference in social isolation scores between the pretest and posttest, with a significance value of 0.003 (<0.05). The average pretest score of 182.00 (very high) decreased to 108.33 in the posttest (moderate). Therefore, CBT-based group counseling services with cognitive restructuring techniques statistically demonstrated a decrease in social isolation levels in the study subjects.